Using a multi-method, user centred, prospective hazard analysis to assess care quality and patient safety in a care pathway - Escoto Kamisha; Hutchinson Allen; Dean Joanne E; Lawson Rod (BMC, 2007)
Abstract Background Care pathways can be complex, often involving multiple care providers and as such are recognised as containing multiple opportunities for error. Prospective hazard analysis methods may be useful for evaluating care provided across primary and secondary care pathway boundaries. These methods take into account the views of users (staff and patients) when determining where potential hazards may lie. The aim of this study is to evaluate the feasibility of prospective hazard analysis methods when assessing quality and safety in care pathways that lie across primary and secondary care boundaries. Methods Development of a process map of the care pathway for patients entering into a Chronic Obstructive Pulmonary Disease (COPD) supported discharge programme. Triangulation of information from: care process mapping, semi-structured interviews with COPD patients, semi-structured interviews with COPD staff, two round modified Delphi study and review of prioritised quality and safety challenges by health care staff. Results Interview themes emerged under the headings of quality of care and patient safety. Quality and safety concerns were mostly raised in relation to communication, for example, communication with other hospital teams. The three highest ranked safety concerns from the modified Delphi review were: difficulties in accessing hospital records, information transfer to primary care and failure to communicate medication changes to primary care. Conclusion This study has demonstrated the feasibility of using mixed methods to review the quality and safety of care in a care pathway. By using multiple research methods it was possible to get a clear picture of service quality variations and also to demonstrate which points in the care pathway had real potential for patient safety incidents or system failures to occur. By using these methods to analyse one condition specific care pathway it was possible to uncover a number of hospital level problems. A number of safety challenges were systems related; these were therefore difficult to improve at care team level. Study results were used by National Health Service (NHS) stakeholders to implement solutions to problems identified in the review.